2023
DOI: 10.3390/cli11080162
|View full text |Cite
|
Sign up to set email alerts
|

Global and Regional Snow Cover Decline: 2000–2022

Stephen S. Young

Abstract: Snow cover affects the global surface energy balance and, with its high albedo, exerts a cooling effect on the Earth’s climate. Decreases in snow cover alter the flow of solar energy from being reflected away from Earth to being absorbed, increasing the Earth’s surface temperature. To gain a global understanding of snow cover change, in situ measurements are too few and far between, so remotely sensed data are needed. This research used the medium-resolution sensor MODIS on the Terra satellite, which has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
(167 reference statements)
0
1
0
Order By: Relevance
“…The occurrence of this spatial pattern on longer time scales is consistent with previously discovered trends in increasing hydrological droughts in southeastern Europe (Peña-Angulo et al, 2022), as well as the identified causes of warm season droughts due to warm winters with no snow (Brunner et al, 2022). The increased frequency of such winters in the last decades (Young, 2023) has led to the below-average spring floods in most rivers of Ukraine (Blöschl et al, 2019;Snizhko et al, 2023), and the emergence of a stable soil moisture deficit at the beginning of growing season, which contributed to intensification of droughts in spring and summer (Kongoli et al, 2012).…”
Section: Drought Indexmentioning
confidence: 99%
“…The occurrence of this spatial pattern on longer time scales is consistent with previously discovered trends in increasing hydrological droughts in southeastern Europe (Peña-Angulo et al, 2022), as well as the identified causes of warm season droughts due to warm winters with no snow (Brunner et al, 2022). The increased frequency of such winters in the last decades (Young, 2023) has led to the below-average spring floods in most rivers of Ukraine (Blöschl et al, 2019;Snizhko et al, 2023), and the emergence of a stable soil moisture deficit at the beginning of growing season, which contributed to intensification of droughts in spring and summer (Kongoli et al, 2012).…”
Section: Drought Indexmentioning
confidence: 99%